THE NATIONAL CANCER CONTROL PROGRAM: PEDIATRIC ONCOLOGY - M. Yu. Rykov (Rossijskij Vestnik Perinatologii i Pediatrii, 2018)
Due to its cardinal differences from the adult oncology the children's oncology takes a special place in the national cancer control program. The article analyzes up-to-date problems and suggests their solutions. It contains statistical indicators and a three-level model of medical care for children with cancer. The tasks of the national program stated in the article reflect the author's point of view and are to be further discussed.